2023
DOI: 10.1021/acs.inorgchem.3c01302
|View full text |Cite
|
Sign up to set email alerts
|

Core Excitations of Uranyl in Cs2UO2Cl4 from Relativistic Embedded Damped Response Time-Dependent Density Functional Theory Calculations

Abstract: X-ray spectroscopies, by their high selectivity and sensitivity to the chemical environment around the atoms probed, provide significant insights into the electronic structures of molecules and materials. Interpreting experimental results requires reliable theoretical models, accounting for environmental, relativistic, electron correlation, and orbital relaxation effects in a balanced manner. In this work, we present a protocol for the simulation of core excited spectra with damped response timedependent densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…In contrast, TDDFT simulations, which do not capture such relaxations, report peaks that are approximately 20 eV higher than experimental positions . Published 4c-DR-TDDFT calculations by Misael et al show substantial improvement on peak predictions over the TDDFT reported in Table . These simulations included equatorial chloride ligands and the resulting discrepancy in peak positions is reduced to between 11–14 eV.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, TDDFT simulations, which do not capture such relaxations, report peaks that are approximately 20 eV higher than experimental positions . Published 4c-DR-TDDFT calculations by Misael et al show substantial improvement on peak predictions over the TDDFT reported in Table . These simulations included equatorial chloride ligands and the resulting discrepancy in peak positions is reduced to between 11–14 eV.…”
Section: Resultsmentioning
confidence: 92%
“…Gomes et al, later showed that capturing the Cs 2 UO 2 Cl 4 crystal environment more completely through incorporation of the Cs counterions had only a small improvement on predicting the relative position of excited states. A recent 4c-DR-TDDFT simulation of uranyl O K-edge XANES by Misael et al, showed that relative peak positions can be brought into closer agreement with experiment by the inclusion of equatorial chloride ligands. However, this study also showed that the modeling of the counterions as an embedding potential did not significantly alter predictions.…”
Section: Introductionmentioning
confidence: 80%
“…Previous works have shown that modeling X-ray spectra using time-dependent density functional theory (TDDFT) with relativistic corrections is capable of capturing some of the spectral features in uranyl core-excitations and yields qualitatively correct spectra. However, the correlation captured by TDDFT is incomplete, shown by the importance of double excitations in the accurate modeling of M-edge spectra in multireference methods with perturbative spin–orbit coupling. ,, On the other hand, the manifestation of double excitation and its physical characteristics in the uranyl M-edge spectrum remain largely unexplored.…”
mentioning
confidence: 99%